Molecular and structural basis of glutathione import in Gram‐positive bacteria via GshT and the cystine ABC importer TcyBC of Streptococcus mutans. Issue 2 (10th June 2013) - Vergauwen, Bjorn; Verstraete, Kenneth; Senadheera, Dilani B.; Dansercoer, Ann; Cvitkovitch, Dennis G.; Guédon, Eric; Savvides, Savvas N.
Summary: Glutathione (GSH) protects cells against oxidative injury and maintains a range of vital functions across all branches of life. Despite recent advances in our understanding of the transport mechanisms responsible for maintaining the spatiotemporal homeostasis of GSH and its conjugates in eukaryotes and Gram‐negative bacteria, the molecular and structural basis of GSH import into Gram‐positive bacteria has remained largely uncharacterized. Here, we employ genetic, biochemical and structural studies to investigate a possible glutathione import axis in Streptococcus mutans, an organism that has hitherto served as a model system. We show that GshT, a type 3 solute binding protein, displays physiologically relevant affinity for GSH and glutathione disulfide (GSSG). The crystal structure of GshT in complex with GSSG reveals a collapsed structure whereby the GS‐I‐leg of GSSG is accommodated tightly via extensive interactions contributed by the N‐ and C‐terminal lobes of GshT, while the GS‐II leg extends to the solvent. This can explain the ligand promiscuity of GshT in terms of binding glutathione analogues with substitutions at the cysteine‐sulfur or the glycine‐carboxylate. Finally, we show that GshT primes glutathione import via thel ‐cystine ABC transporter TcyBC, a membrane permease, which had previously exclusively been associated with the transport ofl ‐cystine.